High-dose mefloquine in the treatment of multidrug-resistant falciparum malaria. - ter Kuile, F; Nosten, F; Thieren, M; Luxemburger, C; Edstein, MD; Chongsuphajaisiddhi, T; Phaipun, L; Webster, H; White, N (1992)
The therapeutic efficacy and toxicity of a high-dose (25 mg/kg) mefloquine regimen (M25) and the currently recommended regimen of 15 mg/kg (M15) were compared in 199 patients with acute falciparum malaria in an area with deteriorating multidrug resistance on the Thai-Burmese border. The clinical and parasitologic responses were significantly more rapid with M25. The incidence of treatment failures by day 7-9 was 7% for M15 and 1% for M25 (P = .03) and had increased to 40% and 9%, respectively, by day 28 (P < .0001). Overall failure rates were highest in children (P = .02). Parasite clearance times were a good predictor of the therapeutic response; all patients with parasitemia persisting > 5 days after treatment experienced subsequent recrudescence. Side effects were dose-related and included dizziness, anorexia, nausea, vomiting, and fatigue. Although vomiting < 1 h after treatment was more likely in young children, children overall tolerated mefloquine better than adults, and men better than women. The optimum treatment dose of mefloquine in this area is 25 mg/kg.